PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA SISWA KELAS 5 TEMA 3 MAKANAN DAN MINUMAN SEHAT - Devi Lorenza, Adella; Wahyuni, Ayu; Agung Juwantara, Ridho (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
The aims of this research are to: (1) find out the dietary habit students of grade V and VI of grade Elementary School students (2) find out the nutritional status students of grade V students of Elementary School. This is survey research and the method of collecting data in the form charging food frequency Questionnare (FFQ) and measurement of body weight and height of stundent. Analysis of data used is descriptive. The results of this re search are: (1) the dietary pattern student of grade V the mostly consumed are staple food, animal side dish, vegetable side dish, vegetable, fruit, and milik. are rice (98%), tempeh (34%), broccoli (8%), orange (22%), milk (40%) (2) the nutritional status students of grade IV, V and VI students of Mangunan Elementary School year 2017 are underweight (4%), normal (86%), overweight (10%), and obesity is none.